(untitled) (American Journal of Research in Humanities and Social Sciences, 2022)
This article presents the ideas of the gradual development of the relationship between society and nature. The meaning of the concept of the noosphere is based on its importance in harmonizing all the spiritual aspects of the human mind and personality in general.